2015
DOI: 10.1002/jssc.201400896
|View full text |Cite
|
Sign up to set email alerts
|

Porous‐membrane‐protected polyaniline‐coated SBA‐15 nanocomposite micro‐solid‐phase extraction followed by high‐performance liquid chromatography for the determination of parabens in cosmetic products and wastewater

Abstract: A SBA-15/polyaniline para-toluenesulfonic acid nanocomposite supported micro-solid-phase extraction procedure has been developed for the extraction of parabens (methylparaben, ethylparaben, and propylparaben) from wastewater and cosmetic products. The variables of interest in the extraction process were pH of sample, sample and eluent volumes, sorbent amount, salting-out effect, extraction and desorption time, and stirring rate. A Plackett-Burman design was performed for the screening of variables in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…A slight shift to a lower angle and lower intensity is due to a decrease in the mesoscopic order of the materials and mainly due to the contrast matching between the silicate framework and organic moieties located inside the porous materials channels (Fig. 3 a and b) [17,39 ].…”
Section: Nh2@mn(tcpp)oac] and [Sba-15-long-chain-nh2@mn(tcpp)oac)]mentioning
confidence: 97%
See 2 more Smart Citations
“…A slight shift to a lower angle and lower intensity is due to a decrease in the mesoscopic order of the materials and mainly due to the contrast matching between the silicate framework and organic moieties located inside the porous materials channels (Fig. 3 a and b) [17,39 ].…”
Section: Nh2@mn(tcpp)oac] and [Sba-15-long-chain-nh2@mn(tcpp)oac)]mentioning
confidence: 97%
“…The supporting of the large metal complexes such as metalloporphines through an organic spacer onto the mesoporous materials is often preferred and also, the solidity of the attachment to the support is an important factor that should be considered during immobilization process [10,19]. Among different mesoporous silica, Santa Barbara Amorphous (SBA-15) due to its unique properties such as thick walls (4-6 nm), thermal and mechanical stability, highly ordered mesostructure, large specific surface area (above 1000 m 2 /g) and regular 2D hexagonal array of channels with a narrow pore-size distribution of 1.5-300 Å has attracted more attentions as solid support [17,[20][21][22][23]. The functionalization and modification of SBA-15 could enhance its capability as a support for supporting the large metal complexes such as metalloporphines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of salt to aqueous sample may cause diverse effects (salting‐out, salting‐in, or no effect), which mainly depends on the physicochemical characteristics of analytes and salt concentration. In some cases, the addition of about 20% w/v NaCl is suitable for SPME, and the results indicated that salting‐out effect facilitated the extraction of preservatives and antioxidants in cosmetics .…”
Section: Sample Preparation Techniquesmentioning
confidence: 99%
“…Great attention has been given to silica particles during the past few decades due to its extensive application in various fields such as pharmacy , electronic and thermal insulators , antireflective coating materials , cosmetics , and diagnostic substances . Since different silica particle sizes make a great difference in its physical, electrical, and optical properties, it is necessary to pay special attention to the effective methods for preparing silica particles with low polydispersity (PDI).…”
Section: Introductionmentioning
confidence: 99%